UPAYA MENINGKATKAN HASIL BELAJAR MATEMATIKA MELALUI MODEL STAD BERBANTUAN MEDIA “BEKAPANG” - Nurul Munna Wahyuningsih; Febriana Dwi Safitri; Tria Mardiana; Septiyati Purwandari (EMTEKA: Jurnal Pendidikan Matematika, 2024)
T This research aims to improve mathematics learning outcomes through the STAD type cooperative model for class II students at SDN Bantul. This research uses the STAD model assisted by BEKAPANG media. This research is classroom action research (PTK) which consists of 2 cycles. Each cycle consists of planning, observation, and reflection. The subjects in this research were 28 class II students consisting of 15 boys and 13 girls. The object of this research is improving learning outcomes for class II students at SD N Bantul Timur. Data collection techniques include test sheets and observations. Based on the research results, there were 20 students out of 28 students who had not reached the KKM score (75) before implementing the STAD type cooperative learning model assisted by BEKAPANG media in the mathematics subject of subtraction material. Student learning outcomes increased after the learning process in cycle I with learning outcomes of 71.41%. In cycle II students had learning outcomes of 92.85%, so there was an increase in students. So it can be concluded that the mathematics learning process through the STAD model assisted by BEKAPANG media has been successfully used to improve student learning outcomes.